DAKWAH POLITIK ISLAM ABDURRAHMAN WAHID DI ERA REFORMASI - Khotimah (El-Hamra, 2018)
Ulama politics has a different pattern from the politics of statesmen, intellectuals an cultural observers because the ulama politics is actually based on the element of da'wah or the term is "preaching through politics". Many religious leaders and scholars who entered the political world, one of which was K.H. Abdurrahman Wahid or better known as Gus Dur. Paradigmatically, Gus Dur's political thinking departed from the rules of fiqh which read: tashharruf al-imam ?ala alra'iyyah manuuthun bil mashlahah (the policy of a leader related to the welfare of the people). Thus, as long as Gus Dur takes part in Indonesian politics, of course there are religious interests that he carries, namely peace, prosperity, democracy and humanitarian independence (HAM) for the benefit or benefit of the ummah.Key Words: Islamic Politics Da'wah, Adbdurrahman Wahid, Reform